2021
DOI: 10.1007/s11686-021-00453-w
|View full text |Cite
|
Sign up to set email alerts
|

Human Cystic Echinococcosis in Lebanon: A Retrospective Study and Molecular Epidemiology

Abstract: Purpose Human cystic echinococcosis (CE) is a zoonotic parasitic disease that constitutes a public health challenge and a socio-economic burden in endemic areas worldwide. No specific surveillance system of CE infections in humans exists in Lebanon. The incidence and trends over time have not been documented. The current study aimed to assess the demographic and epidemiologic features of human CE surgical cases over a 14-year period in the five main regions of Lebanon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…According to a study by Khan et al, only 1.19% of cysts were in these two organs [ 7 ]. In a separate study by Joanny et al, the liver and lung were involved in 0.89% of CE cases [ 8 ]. In contrast, an older study by Dogan and colleagues demonstrated that simultaneous involvement of the lung and liver occurs in approximately 10% of cases in a cohort of 1055 patients with hydatidosis treated surgically [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study by Khan et al, only 1.19% of cysts were in these two organs [ 7 ]. In a separate study by Joanny et al, the liver and lung were involved in 0.89% of CE cases [ 8 ]. In contrast, an older study by Dogan and colleagues demonstrated that simultaneous involvement of the lung and liver occurs in approximately 10% of cases in a cohort of 1055 patients with hydatidosis treated surgically [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CE may develop in more than two organs, but these cases occur extremely rarely [ 10 ]. Clinical course is usually asymptomatic, until the lesion starts to compress surrounding structures or the cyst ruptures [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Egyptian population, residency in rural areas, occupation (farmers and housewives), and age (30–40 years) were significant factors for acquiring CE ( Salama et al., 2014 ). Likewise, high prevalence rates were recorded in the age group of less than 40 years in Iran, Lebanon and Turkey ( Akalin et al, 2014 ; Mahmoudi et al, 2019 ; Joanny et al, 2021 ).…”
Section: Risk Factors Associated With Ce In Egyptmentioning
confidence: 98%